Impact of The Covid-19 Pandemic On West Sumatra Tourism - Arivetullatif; Sulastri; Afrianti, Rini (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the impact of the Covid-19 pandemic on tourism in West Sumatra. This type of research is quantitative research. This study uses secondary data from the official website https://dispar.sumbarprov.go.id for 2019–2020. While the data analysis technique uses descriptive statistics, classical assumptions, multiple linear regression analysis and statistical tests (t test, F test and coefficient of determination). The results showed that the hotel variable had a significant and significant effect on culinary tourism in West Sumatra Province, with a significance value of 0.004 which was smaller than the 0.05 significance level, while the tcount value was 3.080>ttable 2.032, the communication variable had no effect and was not significant on culinary tourism in West Sumatra Province, with a significance value of 0.157 more than a significance level of 0.05, while a tcount value of 1.446<ttable 2.032, the variable of tourist visits has an influence and is significant on culinary tourism in West Sumatra Province, with a significance value of 0.042 less than a significance level of 0.05 , while the tcount value is 2.111>ttable 2.032 and the variables of hotel, communication, tourist visits simultaneously affect culinary tourism in West Sumatra Province, with a significant value of 0.018 which is smaller than α = 0.05 while the Fcount value is 3.819>Ftable 4.53. The Adjusted R Square test results in this study obtained a value of 18.60. This shows that the contribution of the hotel, communication, and tourist visits variables is 18.60% to culinary tourism in West Sumatra Province. While the remaining 72.40% is influenced by other factors not examined in this study.